PENGARUH PENGEMBANGAN PEGAWAI TERHADAP PRESTASI KERJA DI KANTOR CAMAT TOBELO KABUPATEN HALMAHERA UTARA - LIANDO, ROI; LENGKONG, FLORENCE DAICY; RARES, JOYCE JACINTA (Sam Ratulangi University, 2018)
Abstrak : The purpose of this study is to test and analyze the influence of career development towards theaccomplishment of work. The population in this study was an employee of the Office of head of TobeloNorth Halmahera Regency. Population that is, 34 employees. The number of samples that is as much as 34respondents, using the method of stratified random sampling propotional. This research uses a simpleregression analysis tool (simple regression). This research resulted in summary, that career development apositive significant effect against the achievements of the work of employees.Keywords: career development, work achievement